Mariconas : itinerários da velhice travesti, (des)montagens e (in)visibilidades - Nogueira, Francisco Jander de Sousa (2013)
This thesis aims to understand how the subjects that are identified as "mariconas", "Irenes", "aunts" and "old fags" deal with the processes of aging and old age. I seek to further analyze from the biographical narratives (KOFES, 2001), the meanings and the senses that are attributed to their bodies. Faced with new social and body itineraries multiple devices are triggered _ in order to "camouflage" and "circumvent" the prejudice accumulated inside the experience, due to the stigma for being transvestites and now in the condition of elderly. In old age transvestite, social and cultural elements begin to question the existence of a chronological, biological and generational, not even denying the completely. The transvestites that somehow are linked to prostitution, when they survive the streets and violence, built others spaces of sociability. Although marked by silence and invisibility, they create and pass through other places, as new spaces of prostitution, the own house, by militancy, and still build subterfuge, which allow them to move more fluidly and exercise their sexual practices. This ethnographic study was woven from a field survey in Fortaleza and Lisbon, through semi-structured interviews and participant observation / floating (MALINOWSKI, 1978; GOLDMAN, 1995) in bars, nightclubs, cafes, saunas, porn cinemas , households, associations, health services and in the streets and avenues where transvestite routinely prostitutes . In this regard, we note that the bodies of the old transvestites eventually present itself as fields flows and intensities that makes us doubt every fact that you are drawn to. Intend limits. Fissuring structures. Cleaving senses and break the linearity and the challenges that aging can be a place of privileged challenge to gender and sexuality norms as they realize that every moment transvestites build up and rebuild themselves from the experience device (SCOTT, 2009; FOUCAULT, 2001).